Regulation of tyrosine phosphorylation cascades by phosphatases: What the actions of vanadium teach us - Hulley, P; Davison, A (2003)
Protein phosphorylation and dephosphorylation regulate much of the machinery of the cell. Emphasis in recent years has swung toward regulation by dephosphorylation. Much current research focuses on protein tyrosine phosphatases. Researchers of cellular regulation use vanadium as a probe because of its unparalleled ability to selectively inhibit protein tyrosine phosphatases at submicromolar concentrations. This review focuses on the biological actions of vanadium relevant to cellular regulatory cascades. Recent research has led to identification of control points and possible drug targets in 1) the glucose control mechanisms downstream from insulin receptors; 2) pathways regulating mitogenesis, tumor promotion, and other events downstream from growth factor receptors; 3) regulation of osteogenesis and possibilities for counteracting the bone damaging actions of glucocorticoids. An up-to-date understanding of the mechanisms by which vanadium acts and of its currently identified targets is prerequisite to the intelligent design of experiments of this kind. In this review, we will consider mechanisms at the enzymological level, in cellular regulatory cascades, and events affecting the cell or organism as a whole. © 2003 Wiley-Liss, Inc.